From art to insight: The role of a creative arts therapies group workshop on college students' well-being, self-awareness, and loneliness - Arriaga, P.; Simões, M. P.; Marques, S.; Freitas, R.; Pinto, H. D.; Prior, M. P.; Candeias, S.; Rodrigues, M. (The Arts in Psychotherapy, 2024)
This study examined the effects of a three-hour Creative Arts Therapies (CATs) group workshop on perceived well-being, self-awareness, and loneliness among college students. Using a within-subjects design, participants completed surveys before and after the workshop and during a follow-up phase. Each workshop, facilitated by two certified art therapists, involved groups of 5 to 13 students. The workshops included 89 students aged 18–51 years, 87 responded after the workshop and 59 during the follow-up. Results indicated a short-term increase in subjective well-being, characterized by heightened positive emotions, life satisfaction, and reduced negative affect. Additionally, the workshop reduced state anxiety and enhanced awareness, fostering both inward self-awareness of feelings and thoughts and outward environmental awareness. A decrease in concerns about social judgments and feelings of loneliness suggested greater self-acceptance and social connection. Predictors of these changes included the perceived therapeutic value of the workshop and group cohesion. Moreover, depressive symptoms were associated with both negative affect and public self-awareness changes. However, follow-up revealed that increases in life satisfaction and loneliness were transient, returning to initial levels, suggesting the need for ongoing interventions and further research on the effects of CATs in group settings.